Robots and the skill premium: An automation-based explanation of wage inequality - Clemens Lankisch; Klaus Prettner; Alexia Prskawetz (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We analyze the effects of automation on the wages of high-skilled and low- skilled workers and thereby on the evolution of wage inequality. Our model explains the simultaneous presence of i) increasing per capita GDP, ii) de-clining real wages of low-skilled workers, and iii) an increasing skill-premium. These developments are consistent with the experience in the United States over the past decades and have the potential to contribute to the explanation of the rise in overall incomeinequality that we have observed since the 1980s.
urn:nbn:de:bsz:100-opus-14134
Keywords: O11; O41; I24; 330; automation; declining real wages of low-skilled workers; income inequality; long-run economic growth; skill premium